Epitope mapping of lyssavirus structural proteins. - Elmgren, Lindsay Dorn. (University of Ottawa (Canada), 1999)
Lyssavirus specific monoclonal antibodies (Mabs) were used in competitive ELISAs to topographically map two major structural proteins of representative viruses of each of the six lyssavirus genotypes. This is the first description of topographical mapping of lyssavirus proteins based upon competitive Mab binding. A panel of anti-glycoprotein Mabs, all generated against rabies viruses, was used to map antigenic sites on lyssavirus glycoproteins. These Mabs identified thirteen unique epitopes that define four major antigenic sites and two antigenic sub-sites. Glycoprotein antigenic sites were found to be highly conserved throughout all lyssavirus genotypes. Thirty-four unique epitopes were identified on lyssavirus nucleoproteins using a panel of Mabs comprised of representative Mabs generated against nucleoproteins of all lyssavirus genotypes. The panel of anti-nucleoprotein Mabs used in this study revealed five major antigenic sites that again were largely conserved in all lyssavirus genotypes. The epitope variability of the nucleoprotein was much greater than that of the glycoprotein, confirming previous Mab studies of lyssaviruses. Mabs to several epitopes of both structural proteins studied were lyssavirus specific, while at least one anti-nucleoprotein Mab for each lyssavirus was genotype specific with the exception of genotype 5 (European bat lyssavirus type 1). Most of the epitopes identified on both proteins were conformational, however, certain linear epitopes identified in this study that are lyssavirus specific may be useful for diagnosis and vaccine development. Genotype specific epitopes will be useful epidemiologically. The competitive antigenic analysis of the glycoprotein and nucleoprotein support the published phylogenetic relationships of the lyssavirus genotypes. Two of the African lyssaviruses (Mokola virus and Lagos Bat virus) are the furthest diverged of the lyssaviruses. The nearly identical topographical maps of the antigenic sites of both the glycoprotein and nucleoprotein strongly suggest that lyssaviruses have evolved from a common rhabdovirus ancestor. Further, this ancestral rhabdovirus was probably a bat virus.
Keywords: Biology, Microbiology.